Assessment of the prevention and problem solving of drug problem with participation in schools under the local administrative organization in Sisaket province - Phuttanu, Vivat; Cain, Parisha Marie; Kaewhanam, Kathanyoo; Kaewhanam, Phimlikid (Asian Journal of Education and Training, 2024)
The objectives of this research were (1) to assess the suitability and feasibility of participatory approaches for the prevention and solution of drug problems of schools under Sisaket Provincial Administrative Organizations and (2) to create a consensus proposing a leadership development model that influences driving effectiveness, management and performance on drug prevention of schools under the local government organization. The informants were the study administrators and teachers who were responsible for prevention and correction drug problem of school, each group of 5 people, and the total of 10 people, obtained by purposive selection. The research instrument was a semi-structured interview. The interviews were conducted during January to March 2023. The research results showed that (1) Participatory approaches for the prevention and solution of drug problems of schools under the local administrative organizations in Sisaket Province of every created item had a suitability assessment at a level higher than the specified criteria and the possibility of implementing the guidelines; and (2) leadership development model that influences management and results of drug prevention operations in schools under the local government organization can be summarized in 5 issues: (1) raising awareness and education (2) developing communication skills (3) building trusted teams (4) being a good role model, and (5) self-reflection and assessment.